Teaching the Visual Arts in a pandemic context: Interlocutions for Emergency Remote Teaching (Palíndromo, 2022)
The article discusses the Teaching of Visual Arts, from a school in Betim-MG, during the pandemic caused by the new coronavirus. The activities offered, at first, can be taken as a starting point to reflect on the challenges that are emerging in relation to the construction of knowledge in Art in the context of Emergency Remote Teaching. This article seeks to resume the debate of some relevant aspects of Art Teaching, such as the Triangular Approach, the potential of unforeseen events and the experiences brought by students to provide significant learning opportunities, extended objects, the incitement to artistic creation through Contemporary Art, Installation as an artistic praxis leading to the deconstruction of spaces and ideas in the domestic environment. Finally, some distinctions between Emergency Remote Teaching and Distance Education are presented, concluding that the interaction, especially the one carried out in person between individuals, has a central role in the process of internalization of knowledge. The main authors worked are Antunes (2020), Pimentel (2011), Zamperetti (2021) among others.
Keywords: Teaching Visual Arts; Emergency Remote Teaching; Contemporary art; Artistic Installation; Distance Education